Business environment, human capital structural upgrading, and economic development quality - He, Shengbing; Yao, Huilin (Frontiers in environmental science, 2022)
To verify the importance of optimizing a business environment and improving the level of human capital structure to promote economic development, this study employs a panel data of 30 Chinese provinces from the period 2008–2019 and utilizes the spatial Durbin model and quantile regression model to analyze the relation between a business environment, human capital structure upgrading, and economic development quality. We find that the quality of economic development has a strong spatial correlation and the improvement in the business environment promotes human capital structural upgrading and economic development quality. Human capital structural upgrading plays a significant intermediary role, through which improvement in the business environment affects economic development quality. Considering the huge differences in the level of economic development in different regions of China, we also conduct a regional heterogeneity analysis. We find that the promotion effects of the business environment and advanced human capital structure on economic development quality are significant within the sample period, and their promotion effects are significantly heterogeneous and asymmetric across quartiles, indicating that there is heterogeneity in the intensity of dependence of economic development quality on advanced human capital structure and business environment at different stages of economic development. Moreover, by observing the impact trends in the eastern, central, and western regions, we find that the impact of the business environment and human capital structure on the quality of economic development varies somewhat across provinces. This suggests that the eastern and central regions need to strengthen the optimization of the business environment, while the eastern and western regions should pay more attention to the improvement of the level of the advanced human capital structure.